Potassium Fractions in Soil and Response of Cauliflower (Brassica oleracea var. Botrytis) in Coarse Textured Soils of Rangareddy District - and P. Chandrasekhar Rao, K. Kalyani, V. Sailaja (Journal of the Indian Society of Soil Science, 2015)
Coarse textured soils of Rangareddy district were collected from thirty locations and analyzed for potassium (K) fractions. A greenhouse experiment was conducted with the collected soils to know the response of cauliflower to K application. The level of extraction of K by different extractants followed the order: boiling HNO3 (1 M) > NaBPh4 (0.2 M) > citric acid (0.01 M) > NH4OAc (NN) > oxalic acid (0.01 M) > acetic acid (0.01 M). The amount of K extracted by different extractants was more in sandy clay loam soil of Mominpet and very low in sandy soils of Emamguda. The NH4OAc extracted an amount of 54.2 to 242.3 mg kg-1 with an average of 130.3 mg kg-1 and it showed highly significant correlation with 0.2 M NaBPh4 extractable K (r = 0.926**), plant K uptake (r = 0.931**) and also with curd yield (r = 0.975**) of cauliflower. The mean K uptake in the soils ranged from 0.65 g plant-1 on Emamguda soils to 1.67 g plant-1 on Mominpet soil. Mean curd yield was 352.4 g plant-1 in the control which showed a significant increase to 454.8 g plant-1 with the application of 66.6 mg K2O kg-1 soil. The mean response to the application of K was 25.3 kg cauliflower curd per kg of K applied.